Antibacterial Screening of Gunnera perpensa-Mediated Silver Nanoparticles - Naazlene Patel; Kabange Kasumbwe; Viresh Mohanlall (Journal of Nanotechnology)
The biosynthesis of nanoparticles has become quite popular and has been proposed as an alternative over the tedious, expensive, and toxic physical and chemical methods of synthesis due to its cost-effectiveness and ecofriendliness. This study involved the biosynthesis, characterization, and evaluation of the antibacterial activity of Gunnera perpensa-mediated AgNPs. Biosynthesized AgNPs were characterized using TEM, UV, and FTIR spectroscopy. The antimicrobial activity was evaluated in six bacterial strains, using the disc diffusion assay, and MIC was determined using the broth dilution assay. All NPs generally presented as spherical clusters, with sizes ranging from 13 to 24 nm, as determined by TEM. The absorption peaks ranging between 421 and 425 nm and the presence of the C=O bond with amine groups, as indicated by UV and FTIR spectra, confirmed the synthesis and stabilization of G. perpensa extract-mediated AgNPs. Good antimicrobial activity ranging from 7.0 to 9.0 mm was exhibited by both preparations of G. perpensa extract-mediated AgNPs against both Gram-positive and Gram-negative studied bacteria, at MIC ranging from 3.2 to 12.5 μg/ml. Overall, good antibacterial activity was achieved at lower doses with both preparations of the G. perpensa-mediated AgNPs against all tested bacterial strains, suggesting G. perpensa-mediated AgNPs as good antimicrobial agents.